Crop Yield and Soil Fertility Status of Long-Term Rice-Rice-Wheat Cropping Systems - Rawal, Nabin; Ghimire, Rajan; Chalise, Devraj (International Journal of Applied Sciences and Biotechnology, 2017)
Balanced nutrient supply is important for the sustainable crop production. We evaluated the effects of nutrient management practices on soil properties and crop yields in rice (Oryza sativa L.) - rice - wheat (Triticum aestivum L.) system in a long-term experiment established at National Wheat Research Program (NWRP), Bhairahawa, Nepal. The experiment was designed as a randomized complete block experiment with nine treatments and three replications. Treatments were applied as: T1- no nutrients added, T2- N added; T3- N and P added; T4- N and K added; T5- NPK added at recommended rate for all crops. Similarly, T6- only N added in rice and NPK in wheat at recommended rate; T7- half N; T8- half NP of recommended rate for both crops; and T9- farmyard manure (FYM) @10 Mg ha-1 for all crops in rotation. Results of the study revealed that rice and wheat yields were significantly greater under FYM than all other treatments. Treatments that did not receive P (T2, T3, T7, T8) and K (T2, T4) had considerably low wheat yield than treatments that received NPK (T5) and FYM (T9). The FYM lowered soil pH and improved soil organic matter (SOM), total nitrogen (TN), available phosphorus (P), and exchangeable potassium (K) contents than other treatments. Management practices that ensure nutrient supply can increase crop yield and improve soil fertility status.Int. J. Appl. Sci. Biotechnol. Vol 5(1): 42-50